Peningkatan Produktivitas Bagian Pengepakan Menggunakan Basic Quality Tools di PT. XYZ - Haerul Kustiana; Angling Sugiatna; Dini Yulianti (Sainteks: Jurnal Sain dan Teknik, 2021)
Abstract: This research is the application of quality control tools within the scope of increasing productivity of the packaging department at PT. XYZ. This study aims to determine the factors causing the decline in productivity in the packing warehouse area. The first step of the research is to analyze the input data using a Pareto diagram. The source of problems that occur from outside the packing area are four cases, namely Canceled Delivery, Part Received Without Documents, No Stock and Quality Issue. Meanwhile, for problems that occur from internal packaging, there are two, namely the No Packaging Box and No Operator Entering. By using the Ishikawa diagram and 5 whys, the sources of problems that occur in the internal packing area are analyzed further and obtained several sources of problems that contribute greatly to the decline in productivity in the packaging area, namely the process of purchasing packaging boxes which takes quite a long time and long working hours from the packaging team. Some of the solutions for internal problems offered include changing the carton box procurement process using blanket orders, upgrading the team leader's capabilities with order and budget monitoring capabilities, proposing changes in the production flow for semi-finished goods and a proposal to create a temporary warehouse for semi-finished goods. Abstrak: Penelitian ini merupakan penerapan dari alat pengendalian qualitas dalam lingkup peningkatan produktivitas bagian pengepakan di PT. XYZ. Penelitian ini bertujuan untuk mengetahui faktor penyebab penurunan produktivitas diarea gudang pengepakan. Langkah awal penelitian dengan menganalisa data masukan menggunakan diagram Pareto. Sumber masalah yang terjadi dari luar area pengepakan ada empat kasus yaitu Pengiriman Dibatalkan, Part Diterima Tanpa Dokumen, Stock Tidak Ada dan Ada Issue Kualitas. Sementara untuk masalah yang terjadi dari internal pengepakan ada dua yaitu Box Pengemas Tidak ada dan Operator Tidak Masuk. Dengan menggunakan diagram Ishikawa dan 5 whys , sumber masalah yang terjadi di internal area pengepakan dianalisa lebih lanjut dan diperoleh beberapa sumber masalah yang berkontribusi besar terhadap penuruan produktivitas di area pengepakan yaitu proses pembelian box pengemas yang memakan waktu cukup lama dan jam kerja yang panjang dari tim pengepakan. Beberapa solusi untuk permasalah internal yang ditawarkan antara lain merubah proses pengadaan karton box dengan menggunakan blanket order, mengupgrade kemampuan team leader dengan kemampuan order dan budget monitoring, mengusulkan perubahan alur produksi untuk barang-barang setengah jadi serta usulan untuk membuat gudang sementara untuk barang setengah jadi.